Towards justice-oriented science teaching: examining the impact of the science capital teaching approach on teachers (UCL Press, 2023)
While several initiatives for justice-oriented pedagogies have been developed and implemented over the years, there is limited understanding of the ways in which teachers, and their practice, are impacted by these. This article presents data documenting the impact of a pedagogical approach - the science capital teaching approach - on a cohort of teachers. The approach, developed over a period of six years working in close partnership with primary and secondary teachers in England, aimed to support teachers to move towards more equitable and socially just pedagogical practice. This article explores the empirical impact of the approach on teacher practice. The data set comprises the experiences of 43 secondary and 20 Primary school teachers from different geographical regions in England, covering both rural and urban schools. Qualitative data include teacher interviews, observations and discussions and indicate that implementation of the approach resulted in a range of changes: (1) a deepened understanding of, and reflection on, issues of power and equity; (2) greater sharing of authorial roles with students; and (3) stronger relationships of trust between students and teachers. The article concludes by arguing that the implementation of the science capital teaching approach has had a positive effect on teachers and has supported their practice of justice-oriented science teaching.